2007
DOI: 10.1111/j.1365-2893.2007.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine mRNA expression in hepatitis C virus infection: TH1 predominance in patients with chronic hepatitis C and TH1–TH2 cytokine profile in subjects with self‐limited disease

Abstract: Many determinants of the immune response have been implied in the pathogenesis of chronic hepatitis C. TH1 and TH2 cytokines play a prominent role in viral infections and a dysregulation of these cytokines could account for viral persistence and evolution of chronic disease. To explore a possible TH1 and TH2 cytokine dysregulation resulting in the inability to terminate hepatitis C virus (HCV) infection, we studied TH1 [interferon (IFN)-gamma, interleukin (IL)-2] and TH2 (IL-4, IL-10) mRNA expression of periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 34 publications
3
41
0
Order By: Relevance
“…Nowadays, it is well established that the host immune response, which is regulated by the host genetic background, plays a prominent role in the natural history of the disease [3,8,52]. A positive correlation between a high level of pro-inflammatory cytokines secreted in response to HCV-related liver injury, and an increased necroinflammatory activity, liver fibrosis or cirrhosis was previously reported [8,10,11,53]. Cytokine production varies among individuals and is associated with certain mutations within the coding and the regulatory regions [27].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nowadays, it is well established that the host immune response, which is regulated by the host genetic background, plays a prominent role in the natural history of the disease [3,8,52]. A positive correlation between a high level of pro-inflammatory cytokines secreted in response to HCV-related liver injury, and an increased necroinflammatory activity, liver fibrosis or cirrhosis was previously reported [8,10,11,53]. Cytokine production varies among individuals and is associated with certain mutations within the coding and the regulatory regions [27].…”
Section: Discussionmentioning
confidence: 92%
“…Clinical research showed the prominent role of T helper cell type 1 (Th1) or pro-inflammatory and type 2 (Th2) or anti-inflammatory cytokines in the pathogenesis of chronic hepatitis C. Indeed, a positive correlation between Th1 cytokine levels or Th1-type cell percentage and histological fibrosis or progressive liver injury in chronic hepatitis C was detected [7]. On the contrary, Th2 cytokines modulate self-inflicted injury by suppressing the Th1 response leading to milder forms of chronic hepatitis C [8][9][10][11]. Actually, in the absence of an efficient eradication of the infected cells, the continuing inflammation is responsible for liver damage leading to fibrosis and ultimately cirrhosis [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, they produce intrahepatic IFN-γ, which has antiviral action and is essential in the action of T-cells [47][48][49].…”
Section: Pathogenesismentioning
confidence: 99%
“…This mechanism can eliminate infected hepatocytes, thereby limiting viral replication and contributing to liver tissue damage during the immune response. The hepatitis C virus has the ability to infect not only hepatocytes but also immune cells such as B and T lymphocytes [48].…”
Section: Pathogenesismentioning
confidence: 99%
“…However, it has been suggested that a strong proinflammatory cytokine response could play an important role in the development of hepatic injury in patients with chronic hepatitis C, and therefore, apart from contributing to viral clearance, this polarized immunological profile may contribute to the pathogenesis of liver disease. Subjects with a self-limiting HCV infection appear to maintain their ability to mount both an inflammatory and a regulatory cytokine response for extended periods following viral clearance [7] .…”
Section: Introductionmentioning
confidence: 99%